A Case of Adrenal Cushing’s Syndrome Presenting as Avascular Necrosis of the Femoral Head - Lee, Yu Hee; Lee, Soon Hee (Highlights on Medicine and Medical Research Vol. 4, 2021)
Avascular necrosis of the femoral head is generally caused by excessive use of steroids or alcohol consumption. Avascular necrosis of the femoral head rarely occurs from the overproduction of endogenous cortisol. This report introduces a case of a 37-year-old female who presented with avascular necrosis of the femoral head and adrenal Cushing syndrome. The biochemical & pathologic examination confirmed a cortisol-producing adrenal adenoma. The patient’s persistent complaint of right pelvic pain resulted in further examinations that confirmed the presence of avascular necrosis of the right femoral head. The patient was discharged after left adrenal resection and total right hip arthroplasty and she has been monitored without relapse. This case report shows that avascular necrosis of the femoral head may appear as an early symptom of endogenous cortisol production.